Negative Regulation of RNF90 on RNA Virus-Triggered Antiviral Immune Responses Targeting MAVS - Yang, Bo; Zhang, Ge; Qin, Xiao; Huang, Yulu; Ren, Xiaowen; Sun, Jingliang; Ma, Shujun; Liu, Yanzi; Song, Di; Liu, Yue; Cui, Yuhan; Wang, Hui; et al. (Frontiers in Immunology, 2021)
The antiviral innate immunity is the first line of host defense against viral infection. Mitochondrial antiviral signaling protein (MAVS, also named as Cardif/IPS-1/VISA) is a critical protein in RNA virus-induced antiviral signaling pathways. Our previous research suggested E3 ubiquitin-protein ligases RING-finger protein (RNF90) negatively regulated cellular antiviral responses by targeting STING for degradation, though its role in RNA virus infection remains unknown. In this study, we demonstrated that RNF90 negatively regulated RNA virus-triggered anti-viral innate immune responses in RNF90-silenced PMA-THP1 cells, RNF90-deficient cells (including HaCaTs, MEFs, BMDMs) and in RNF90-deficient mice. However, RNF90 regulated RNA virus-triggered anti-viral innate immune responses independent of STING. In fact, RNF90 promoted K48-linked ubiquitination of MAVS and its proteasome-dependent degradation, leading to the inhibition of innate immune responses. Taken together, our findings suggested a novel function and mechanism of RNF90 in anti-viral innate immunity.